Widerstand und Beharren: Die Kirchen im Dritten Reich - von Aretin, Karl Otmar (Kirchliche Zeitgeschichte, 1995)
This essay was prompted by the question as to how far the experiences of Germany's second dictatorship, in the former East Germany, throw new light on the Church Struggle during the first, Nazi, period. It has to be admitted that both the major churches, protestant and catholic, were not enamoured of the Weimar Republic's parliamentary democracy. Its overthrow was therefore accepted willingly enough. By signing the Concordat the focus of attention in the Catholic Church turned to legal and diplomatic matters, and left most of the initiative to Rome. By contrast, the attempt to force all the protestant churches to accept the authority of a single Reich Bishop led to the founding of the Confessing Church as the true church. Even though both churches were forced to the sidelines of public affairs, they nevertheless succeeded in maintaining their corps of beliefs, and so were a barrier against the demonic fury of Nazism. During the war, the joint protests of several bishops of both denominations against the iniquitous murder process of the so-called "euthanasia" action had great effect. But it did not lead to any more fundamental challenge to regime, mainly, I suggest, because of the war-time situation. The significance of the churches during the Third Reich, which is also true for the period of Communist domination in East Germany, did not lie in their ability to mobilize any effective resistance but rather in their perseverance in upholding their Christian system of values. The courageous actions of protestant Christians at the end of the East German regime show what effects such perseverance can have.